EU Accession, Domestic Market Competition and Total Factor Productivity. Firm Level Evidence - Klaus S. Friesenbichler (Austrian Institute of Economic Research (WIFO), 2014)
In this paper we argue that changes in the EU membership status of the countries in Central and Eastern Europe led to less concentrated markets. This is due to the implementation of competition policy and other pro-competitive policies embedded in the Community Acquis, the body of European Union law. A regression analysis using data on 39,646 firms from six survey waves between 2002 and 2013 found EU membership to significantly increase the degree of domestic competition. While the effect of competition policy itself on market structures was statistically insignificant, the interaction between EU membership status and competition policy showed a strong and statistically significant competition enhancing effect. These findings were linked to a firm-level TFP analysis. Less concentrated markets were associated with higher productivity levels. This finding is robust after controlling for endogeneity issues. EU membership was only weakly associated with changes in TFP levels, but led to a decrease in the variance of the productivity measure across firms.
Keywords: 330; competition policy; productivity; Community Acquis; EU; Enterprise Surveys; ECA; CEE